(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
In this article, there are special studies on the organization of modern education, the use of convenient methods, the integration of foreign language and chemistry, and the study of chemical terms and at the same time learning these terms in English will be a great incentive for the reader. information about the possibility is given.